2016
DOI: 10.1002/ase.1612
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of traditional versus three‐dimensional augmented curriculum on anatomical learning outcome measures

Abstract: This study examined whether student learning outcome measures are influenced by the addition of three-dimensional and digital teaching tools to a traditional dissection and lecture learning format curricula. The study was performed in a semester long graduate level course that incorporated both gross anatomy and neuroanatomy curricula. Methods compared student examination performance on material taught using lecture and cadaveric dissection teaching tools alone or lecture and cadaveric dissection augmented wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
94
1
7

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 119 publications
(119 citation statements)
references
References 57 publications
4
94
1
7
Order By: Relevance
“…This interactivity allows the user to explore hard‐to‐reach features, including intraosseous structures, such as the paranasal sinuses, while still being able to rotate the model freely and explore the full extent of the structures and their surroundings. Using 3D computer models featuring virtual dissection in conjunction with traditional resources has previously been shown to enhance the learning of anatomy, as compared to using traditional resources alone (Peterson and Mlynarczyk, ; Afsharpour et al, ). However, as noted above, in the current study, the baseline level of gross anatomy knowledge in both the cohorts was low, and, as such, it is possible that students became disoriented when rotating the model and subsequently could not comprehend the sectional views that virtual dissection presents.…”
Section: Discussionmentioning
confidence: 99%
“…This interactivity allows the user to explore hard‐to‐reach features, including intraosseous structures, such as the paranasal sinuses, while still being able to rotate the model freely and explore the full extent of the structures and their surroundings. Using 3D computer models featuring virtual dissection in conjunction with traditional resources has previously been shown to enhance the learning of anatomy, as compared to using traditional resources alone (Peterson and Mlynarczyk, ; Afsharpour et al, ). However, as noted above, in the current study, the baseline level of gross anatomy knowledge in both the cohorts was low, and, as such, it is possible that students became disoriented when rotating the model and subsequently could not comprehend the sectional views that virtual dissection presents.…”
Section: Discussionmentioning
confidence: 99%
“…VR enables 3D projection of color images on the surface of human body, which can now be dissected layer by layer by the use of color transverse sections prepared with cross‐sectional image datasets (Temkin et al, ). Some anatomists are of the opinion that the modern 3D reconstruction and imaging methods give visual impression of internal structures of individual living patients that can be superior to those observed during dissection (Marker et al, ; Yammine and Violato, ; Peterson and Mlynarczyk, ). The study of living anatomy, with the help of advanced imaging modalities, have become an integral part of anatomy education in present times by providing a link between basic gross anatomy and clinical practice.…”
Section: Incorporation Of Advanced Technology and Modern Teaching Metmentioning
confidence: 99%
“…However in terms of knowledge acquisition the choice was not so unanimous (Patel and Moxham, ). Students are also of the opinion that inclusion of 3D learning tools influence long‐term retention of gross anatomy material and hence should be considered as beneficial adjunct to dissection for anatomy courses (Peterson and Mlynarczyk, ). In another study students have reported that textbook reading and working with anatomical models were most important in helping them learn the course material and such an observation supports the role of active learning in gross anatomy alongside dissection‐based teaching (Shaffer, ).…”
Section: Counter Opinion In Favor Of Cadaveric Dissection As a Teachimentioning
confidence: 99%
“…Some examples of virtual reality applications within health science and medical education include: an examination of digital pathology slides using an Oculus Rift DK2 (Farahani et al, ); virtual drug design using gesture‐recognition instead of standard input devices (Norrby et al, ); and a 3D virtual anatomy puzzle using Oculus Rift DK2 (Messier et al, ). The release of modern 3D virtual systems has paved the way for new approaches to medical imaging and education and have demonstrated success as beneficial supplements in anatomical education (Miller, ; Peterson and Mlynarczyk, ).…”
Section: Introductionmentioning
confidence: 99%